RANDOM SIMILARITY EFFECT OF HIGH SCHOOL STUDENTS IN PROBABILITY MATERIAL - Damayanti, Febri Dini Wahyu; Agyatus, Istimewa Septi; Qohar, Abd (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2026)
This article aims to analyze how high school students experience and manifest Random Similarity Effect (RSE) in understanding probability material as a specific form of representative bias. RSE refers to the tendency of students to choose patterns that appear intuitively random even though mathematically all possibilities have equal probability. This study uses an explicit cognitive theoretical approach, focusing on the thinking process and the emergence of cognitive bias. The subjects of the study were 36 students of class XD at SMAN 1 Turen. Data were collected by giving probability problems designed to trigger RSE bias, followed by in-depth interviews with four selected subjects. The analysis was carried out using an indicator rubric to classify students' level of understanding into three levels. The results showed that two subjects were at Level 2 (explicitly affected by RSE), one subject at Level 1 (correct answer without conceptual understanding), and one subject reached Level 0 (understanding the concept of probability logically and free from intuitive bias). These results indicate that most students are still trapped in intuitive reasoning, emphasizing the importance of a teaching approach that encourages reflective thinking and deep understanding of the concept of probability.